Conclusion and Recommendations on The Psychological Conditions of Children and Youth in Lebanon after the July 2006 war - El Amine, Adnan (Beirut Lebanese Association for Educational Studies, 2008)
This study was conducted in the spring of 2007 which was nine months after the July War of 2006 that was initiated by Israel against Lebanon. It included children and adolescents enrolled in kindergartens and public schools. Statistical rules were adopted that can be considered a representative sample of the Lebanese students in terms of sector, province, educational stage, size of the school and gender. This study aimed to assess children and adolescents psychological conditions in terms of their suffering from anxieties and psychological disturbances. This study had two purposes: one is scientific in order to present a new definition on the topic and the second in order to bring about progress in determining the essence of the required moral support to Lebanon s children and adolescents and in order to provide a solid base of knowledge through which a center for psychological support for children and adolescents may be launched.
: Chapter in a Book
Keywords: Children and youth; Enfants et Jeunesse; Guerre Guerre Juillet 2006; Psychological Health; Santé psychologique; War; War July 2006; 2006